2014
DOI: 10.4103/2230-8598.144066
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity in babies weighing <1800 g; with special reference to babies weighing between 1501 and 1800 g: An experience from a tertiary care hospital in Delhi

Abstract: Background: Retinopathy of prematurity (ROP) is a disease related to low birth weight, prematurity, oxygen administration, and various other factors, which are yet to be identifi ed. Aims: The aim was to fi nd incidence of ROP and risk factors for causation in babies weighing <1800 g; and in the babies weighing between 1501 and 1800 g. Design: Prospective study. Materials and Methods: Neonates weighing ≤1800 g taking birth in our institution from January 2011 to January 2012 for a span of 1 year; were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A study done by Charan R et al had screened all babies <1700 gm for ROP. 14 16 The present study was an attempt to find incidence for ROP by newer guidelines from Government of India, published under the Rashtriya Bal Swasthya Karyakram (RBSK) which include screening of all newborns <2 kg and in present study it had shown the significant incidence of ROP in >1.5 kg newborns. 7 In present study incidence of ROP was 24.1% which was similar like in Maheshwari R et al, (20%), Chaudhari S et al, (22.3%) and Goyal A et al, (25.4%).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A study done by Charan R et al had screened all babies <1700 gm for ROP. 14 16 The present study was an attempt to find incidence for ROP by newer guidelines from Government of India, published under the Rashtriya Bal Swasthya Karyakram (RBSK) which include screening of all newborns <2 kg and in present study it had shown the significant incidence of ROP in >1.5 kg newborns. 7 In present study incidence of ROP was 24.1% which was similar like in Maheshwari R et al, (20%), Chaudhari S et al, (22.3%) and Goyal A et al, (25.4%).…”
Section: Discussionmentioning
confidence: 74%
“…Kumar P et al and Kapoor R et al both found Respiratory Distress Syndrome (RDS) as a significant independent risk factor for ROP in multivariate analysis. 5,16 While Maini B et al and Le c et al, on univariate analysis found that by giving complete dose of antenatal steroid, risk of developing ROP were decreased. 15,22 Hence by giving complete dose of antenatal steroid we can prevent occurrence of ROP directly and indirectly by decreasing incidence of Respiratory Distress Syndrome (RDS).…”
Section: Discussionmentioning
confidence: 98%
“…9,11 There have, however, been several reports of ROP in bigger and more mature babies in India. 16,[19][20][21][22] The lower GA, lower BW as well as the lower proportion of babies weighing >1500 g with ROP in this series are a reflection of improved neonatal care.…”
Section: Resultsmentioning
confidence: 79%
“…The incidence and severity of ROP show an inverse relationship with BW and GA, with few cases diagnosed in babies weighing over 1500 g or babies whose GA is >32 weeks at birth. Few reports indicate risk of ROP in mature babies as well [14,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%